Застосування нанотехнологій при експлуатації та ремонті тягових редукторів вагонів метрополітену - Зубенко, Денис Юрійович (Eastern-European Journal of Enterprise Technologies, 2010)
The causes and the process of electric traction reducers wearing . The main directions of the tribology problems development for traction rolling stock have been shown. The prerequisites and the methods of parts durability calculation have been determined